Socıal Capıtal Of Educatıon Wıth A Gender Perspectıve For Polıtıcal Equalıty Of Ethnıc Mınorıtıes Semende - Handi Mulyaningsih (Cita Konsultindo Research Center, 2024)
Equality in politics is necessary to improve the welfare of both men and women. The Gender Empowerment Index or IPG of Lampung Province in 2020 was 90,330; in 2021, it was 90,370; in 2022, it was 90,580. This increase was followed by an increase in the Human Development Index (HDI) in 2021 by 69.90, in 2022 by 70.45, in 2023 by 71.15. The average length of schooling increased from 8.08 in 2021, 8.18 in 2022, and 8.29 in 2023. Gender equality improves well-being and education. This study explains the gender gap in education in Semende ethnicity and its impact on patriarchal values that hinder the development of gender equality in the political field. The research was conducted with qualitative methods of gender approaches on access, control, participation and benefits. Data was collected through interviews and secondary data. The results showed that formal education has yet to be able to exclude students from patriarchal culture. In addition, education within the family and environment strengthens patriarchal culture. Factors of educational facilities, the number of teachers, the distance of schools from settlements, and language and ethnic values are obstacles to developing gender equality education. In addition, the development of gender equality in Semende Ethnicity shrinks the roles of women in politics.